2018
DOI: 10.1016/j.scitotenv.2018.03.253
|View full text |Cite
|
Sign up to set email alerts
|

Investigating in-sewer transformation products formed from synthetic cathinones and phenethylamines using liquid chromatography coupled to quadrupole time-of-flight mass spectrometry

Abstract: Recent studies have demonstrated the role of biofilms on the stability of drug residues in wastewater. These factors are pertinent in wastewater-based epidemiology (WBE) when estimating community-level drug use. However, there is scarce information on the biotransformation of drug residues in the presence of biofilms and the potential use of transformation products (TPs) as biomarkers in WBE. The purpose of this work was to investigate the formation of TPs in sewage reactors in the presence of biofilm mimickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Therefore, only 60% of PMMA was (bio)transformed as the sorption and abiotic reactors were used to account for losses through abiotic processes. It is likely that PMMA has a higher rate of degradation in an activated sludge reactor as a previous study involving in-sewer incubation of PMMA in the presence biofilm had 20% loss over 24 h incubation [104]. Two TPs were detected and identified (TP-166 and TP-196) in the biotic reactor (Table 4.3).…”
Section: Identification Of Biotransformation Products Of Pmmamentioning
confidence: 80%
See 4 more Smart Citations
“…Therefore, only 60% of PMMA was (bio)transformed as the sorption and abiotic reactors were used to account for losses through abiotic processes. It is likely that PMMA has a higher rate of degradation in an activated sludge reactor as a previous study involving in-sewer incubation of PMMA in the presence biofilm had 20% loss over 24 h incubation [104]. Two TPs were detected and identified (TP-166 and TP-196) in the biotic reactor (Table 4.3).…”
Section: Identification Of Biotransformation Products Of Pmmamentioning
confidence: 80%
“…In some studies mephedrone levels in wastewater have been reported as below quantification level or absent [106,107,109], more likely due to its significant (bio)transformation under aerobic conditions in-sewer system, as it has been reported [104,113,114]. Additionally, DHM was identified as a major TP from an in-sewer stability experiments and determined to be a reliable biomarker due to its levels within a 24 h residence time [104]. Though DHM has not been monitored in wastewater studies it has been proposed as a biomarker of exposure for mephedrone use in wastewater based epidemiology [104] and has been previously detected in pooled urine samples from UK [115].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations